Analysis of pressure waves in the cone-type combustion chamber under SI engine knock. (15th May 2015) - Yao, Anren; Xu, Han; Yao, Chunde
Highlights: A 3D numerical model is conducted to investigate the shock waves in the engine knock. Overpressure distribution on the top piston surface is caught while knocking. Numerical simulation shows that shock waves converge in the combustion chamber. The converged shock waves damage piston during severe knock. Abstract: For the internal-combustion engine, super knock produced by the engine downsizing technology induces severe oscillations in a combustion chamber, which may damage the piston. In this work, 3D numerical simulation is used to study the propagation and reflection of pressure waves produced in the cone roof type combustion chamber. Overpressure distribution of top piston surface is caught. Numerical simulation shows that the pressure waves are amplified in a special zone because of the shape of the combustion chamber, which induces the overpressure much higher than that in other zones. The numerical results are validated by the damaged pistons. It is found that the converged pressure waves could be the reason which causes damage in the local region of the piston under super knock. The results obtained in the study provide assistance in the design of combustion chamber shape in order to avoid piston destroyed by the pressure waves.